Methodology for assessing the social effectiveness of exhibition activity - Yu. V. Vorontsova; D. S. Garbuz (Вестник университета)
Improving the exhibition activity efficiency is a rather complex and multi-purpose task that requires taking into account many factors and using various methods and tools. To achieve success in this field, it is necessary to apply an integrated approach, considering the relationship between the economic and social effectiveness of exhibition activity, as well as to use innovative technologies and the latest research methods. The article presents the methodology developed by the authors for the quantitative assessment of social efficiency, which is complex and also includes the calculation of the selected elements’ sensitivity of social efficiency to different changes. The indicators’ calculation of the exhibition social significance the makes it possible to assess its impact on society and determine how much it contributes to the development of culture, coverage of topical issues and familiarization of the general population with cultural and scientific achievements. The quantitative assessment methodology of the exhibition activity effectiveness based on the calculation of the social efficiency integral indicator can be supplemented with methods of organizational support of the exhibition process, meta-planning and risk assessment.